Response Based Tunning of Proportional and Integral Constants in PI Controlled Six Phase PMSM Drive - Tomer, Anurag Singh; Dubey, SP (International Journal of Computer Sciences and Engineering, 2025)
This paper deals withthe modeling of six phase Permanent Magnet Synchronous Motor (PMSM) which has been done with the aid of Matlab and then the complete drive system is designed which consists primarily of two inverter and a Proportional integral controller. Proportional-Integral controller is most commonly used in drives system. The combination of proportional and integral is important to increase the speed of response and also to eliminate the steady state error. It also gives the reason of choosing six phase over three phase and superiority of PMSM with other motors like DC motors and Induction motor.Performance analysis with Manual tunningof proportional (Kp) and integral (Ki) constant is studied which shows the best suited value of Kp and Ki in the drive system by of these values.